Distribution patterns and controlling factors of beach bars in Qinghai Lake, NW China - Peng, Biao; Xu, Zhengjian; Chen, Xiaowan; Zhao, Yonghua (Frontiers in Earth Science, 2024)
The significance of beach-bar reservoirs, which are intricately linked to unconventional hydrocarbon reservoirs, has gained increased attention. This study elucidates the complex mechanisms governing the formation, spatial distribution, and morphological characteristics of beach bars in Qinghai Lake, NW China, highlighting the interplay of lake-level fluctuations, wind wave dynamics, sediment provenance, and terrain gradient. Our findings reveal that large-scale lake-level fluctuations primarily dictate the initial formation settings of beach bars, while small-scale fluctuations refine their internal stratification and sedimentary features. Wind wave dynamics play a critical role in defining suitable depth zones for beach bar development, influencing their morphology and resulting in distinct sedimentary characteristics across different lake zones. Furthermore, the study categorizes beach bars into three main systems based on sediment provenance—bedrock, alluvial fan (fan delta), and braided river systems—each exhibiting unique compositional and structural attributes. Terrain gradient around the lake significantly affects beach bar formation, with areas having a gradient less than 0.7 degrees being particularly favorable. This research advances our understanding of lacustrine beach bar dynamics, offering insights into their potential as indicators of past environmental conditions and their implications for hydrocarbon exploration. The comprehensive analysis of controlling factors provides a foundation for predicting beach bar distribution and contributes to the broader field of sedimentary geology by integrating multi-disciplinary approaches to study lacustrine sedimentary processes.